(untitled) (Economic studies journal, 2025)
This study aimed to assess the extent to which Libyan public institutions subject to the oversight of the Libyan Audit Bureau comply with governance principles, in accordance with the Governance Guide for the Banking Sector issued by the Central Bank of Libya in 2010, and the governance rules issued in 2010 under the Libyan Commercial Law. This was based on the audit results contained in the Libyan Audit Bureau’s reports. To achieve this objective, the researchers used a content analysis approach to examine the 2022 and 2023 reports of the Libyan Audit Bureau, focusing specifically on the investment and banking sectors. The analysis revealed weak and declining governance indicators, along with the absence of mechanisms to ensure the proper implementation of governance rules as stipulated in legislation and laws. This has created an environment conducive to negative governance practices and inefficiency, with numerous violations reported and all governance indicators showing negative performance. There is also a noted weakness in governance mechanisms within corporate organizational structures, including the absence of clear policies such as risk management and compliance policies. Furthermore, there is a lack of independence among boards of directors amid the absence of effective internal oversight. The principle of disclosure and transparency remains one of the major challenges in the Libyan institutional sector—particularly regarding timing, proper disclosure, delays in the approval of financial statements, and the consolidation of financial reports for the fiscal years ended. There is also a delay in the preparation of final accounts and annual budgets. Based on these findings, the researchers recommend raising awareness of the importance of adopting governance concepts and principles in Libyan public institutions. It is also essential to hold training courses or offer professional certifications specializing in governance, and to develop qualified professional cadres with a deep understanding of governance practices to enhance their application within Libyan public institutions